The Feasibility and Efficacy of Social Cognition and Interaction Training for Outpatients With Schizophrenia in Japan: A Multicenter Randomized Clinical Trial - Kanie, Ayako; Kikuchi, Akiko; Haga, Daisuke; Tanaka, Yuki; Ishida, Akina; Yorozuya, Yuko; Matsuda, Yasuhiro; Morimoto, Tsubasa; Fukuoka, Tomoharu; Takazawa, Satoru; Hagiya, Kumiko; Ozawa, Sachiyo; et al. (Frontiers in Psychiatry, 2019)
Background: Schizophrenia is a disabling illness. Social Cognition and Interaction Training (SCIT) seeks to improve patients’ social functioning by alleviating deficits in social cognition. SCIT has shown promise in improving social cognition in patients with schizophrenia, but has not yet been studied in Japan. Design: An assessor-masked, randomised, parallel-group clinical trial was conducted to compare the feasibility and efficacy of SCIT with treatment as usual (TAU). Setting: Participants were recruited from outpatient clinics at the National Center of Neurology and Psychiatry and four other hospitals in Japan. Participants: Seventy-two patients diagnosed with schizophrenia or schizoaffective disorder consented to participate in the trial. Procedure: Participants were randomly allocated to either a SCIT subgroup or a TAU subgroup. SCIT is a manual-based group intervention that is delivered in 20–24 hour-long weekly sessions. Groups include two to three clinicians and four to eight patients. Hypotheses: We hypothesised that SCIT would be found to be feasible and that patients who were randomised to receive SCIT would exhibit improvements in social cognition. Results: Data from 32 participants in each subgroup were entered into analyses. The persistence rate in the SCIT subgroup was 88.9%, and the average attendance rate was 87.0%. Intrinsic motivation was significantly higher in the SCIT subgroup than the TAU group during the first half of the program. Mixed effects modelling of various outcome measures revealed no significant interaction between measurement timepoint and group in any measures, including social cognition, neurocognition, symptom severity, and social functioning. In the case of the social cognition measure, significant change was observed only in the SCIT subgroup; however, the interaction between timepoint and group failed to reach significance. In an exploratory subgroup analysis, a shorter duration of illness was found to be associated with significantly better improvement on the social cognition measure in the SCIT subgroup compared with the TAU subgroup. Conclusions: In terms of the primary objective, the relatively low dropout rate observed in the present study suggests that SCIT is feasible and well tolerated by patients with schizophrenia in Japan. This view is also supported by participants’ relatively high attendance and intrinsic motivation.